Examining the Model of Criminal Responsibility for Corporations Perpetrating Environmental Crimes - Muhammad Iftar Aryaputra; Subaidah Ratna Juita; Sukimin Sukimin; Dewi Tuti Muryati; Rahmi Dwi Sutanti; Uche Nnawulezi (Jurnal Pembangunan Hukum Indonesia, 2026)
Environmental crimes are predominantly the responsibility of individuals. However, corporations may also commit environmental offences, given their dependence on natural resources and the waste generated through production processes. This research project aims to analyse the formulation of corporate criminal liability provisions, as well as the patterns of corporate criminal accountability reflected in judicial decisions concerning environmental crimes. The research method is normative legal research using secondary data as the primary source, analysed qualitatively and descriptively. The results indicate that there is no uniform pattern of corporate criminal liability regulation in the environmental sector. Only two laws provide comprehensive regulatory frameworks: Law Number 5 of 1990, as amended by Law Number 32 of 2024, and Law Number 18 of 2013. Meanwhile, court decisions regarding corporate perpetrators of environmental crimes continue to be dominated by the criminalisation of individuals. Interestingly, over the past five years, court decisions in the environmental sector have increasingly criminalised corporations. This finding confirms that the current legal framework recognises corporations as perpetrators of criminal offences in the environmental sector.